Frontal sinus fracture management: a systematic review and meta-analysis. Issue 1 (January 2021) - Johnson, N.R.; Roberts, M.J.
Abstract: A systematic review of the frontal sinus fracture management literature was undertaken to document measurable outcomes, with emphasis on complications associated with the various treatment strategies. A comprehensive electronic search was undertaken in October 2018. Randomized controlled trials (RCT), controlled clinical trials, retrospective and prospective studies describing the management of frontal sinus fractures and complications were included. Twenty-four publications were included: one reporting a prospective RCT and 23 reporting consecutive case series studies (four prospective, 19 retrospective). These included 2388 patients (84.1% male, average age 23–43 years); 50.7% of cases were due to motor vehicle accidents and 61.8% had a concomitant intracranial injury. There were six categories for anterior table reconstruction, three endoscopic surgery categories, 11 for obliteration, and six for cranialization. Forest plots demonstrating complications based on the Clavien–Dindo classification of 1 ('low') and >3 ('high') were determined for total, early, and late complications, with heterogeneous effect sizes. Fractures with a nasofrontal outflow tract (NFOT) injury without obstruction can be treated with reconstruction if displaced, or managed conservatively if undisplaced. Obliteration and cranialization should be considered when there is obstruction of the NFOT. A computed tomography scan should be performed at 6 months to evaluate re-ventilation of the sinus. Endoscopic sinus surgery is a reasonable salvage re-ventilation procedure.